RESOURCE BASE AS THE BASIS OF SUSTAINABLE TOURISM DEVELOPMENT IN THE PALIĆ NATURE PARK - Trišić, Igor (The Business of Tourism, 2024)
The Palić Nature Park has significant potential in terms of the resource base of sustainable tourism. This resource base forms natural and social motives, which with proper tourism development can contribute to overall sustainability. The subject of research in this work is the resource base that can contribute to the development of sustainable tourism in this protected area. As tourism factors can be of a complementary type, a condition is created for the formation of a unique tourism product. By properly implementing these factors into the tourism offer, and by promoting this destination with its natural and social potential, protection systems can be improved, socio-cultural values can be strengthened and significant economic income can be achieved. A large part of the income can be refinanced into the protection and improvement of the natural and social values of this protected area. At the same time, this constitutes a circular system of sustainable tourism development, in which ecological, economic, socio-cultural and institutional principles of sustainability stand out as important. The qualitative methodology was used in the research. The qualitative methodology included the analysis of various research results, as well as the field examination of resources for the development of sustainable tourism. The results of the research can contribute to the development of planning documents for the development of tourism in the Palić Nature Park and other protected areas.